Down the River, Out to Sea: Mobility, Immobility, and Creole Identity in New Orleans Regionalist Fiction (1880-1910) - Amy Doherty Mohr (European Journal of American Studies)
This essay examines the meaning of mobility in New Orleans regionalist fiction, focusing on Creoles of Color, including Honoré, f.m.c. (free man of color) and Palmyre in George Washington Cable’s The Grandissimes (1880), the ambiguously raced Mariequita in Kate Chopin’s The Awakening (1899), and Victor Grabért, of West Indian ancestry, in Alice Dunbar-Nelson’s “The Stones of the Village” (1900-1910). I argue that each of these characters represents a transnational identity, allowing for a degree of geographic, cultural, and social mobility, beyond the racial divisions imposed by segregation. Considering Davis’s view of New Orleans as “a potential model” (189) for a multiracial and transnational society, I analyze the potential of the hybrid, geographically and socially mobile subject to resist social norms (Bhabha, Soja) as well as the difficulties of such transience. I will address both cultural mobility and immobility, focusing on motifs of migration and exile, considering the associations of the sea with slavery (Gilroy) and the hope for a new way of life.